Narciclasine-4-O-β-D-xylopyranoside, a new narciclasine glycoside from Zephyranthes minuta. Issue 2 (17th January 2020) - Katoch, Deepali; Kumar, Dharmesh; Padwad, Yogendra S; Singh, Bikram; Sharma, Upendra
Abstract: A new narciclasine glycoside, narciclasine-4- O - β -D-xylopyranoside (1 ) was characterised along with four known alkaloids pancratistatin (2 ), 1- O -(3-hydroxybutyryl) pancratistatin (3 ), vittatine (4 ), 9- O -demethylgalanthine (5 ) from Zephyranthes minuta . Their structures were established on the basis of spectroscopic data analysis. The in vitro cytotoxic study of extract, fractions and isolated compounds against two human cancer cell lines (KB and SiHa) indicated the potential activity of extract and n -butanol fraction due to presence of active alkaloids pancratistatin, 1- O -(3-hydroxybutyryl) pancratistatin, lycorine and haemanthamine. Graphical Abstract: